Diagnóstico situacional para Identificar los Posibles problemas Turísticos en el Cantón Saquisilí. - Montatixe Chile, Jessica Alexandra (2019)
In the Cotopaxi province is Saquisilí Canton, a privileged place of natural landscapes, culture, religious festivals, traditions and friendly people. Therefore, we have taken into account the information on the subject. Initially, bibliographic information was collected, such as the Development and Territorial Planning Plan (2014-2019) and the Catastro of attractions and tourist facilities; interviews were also published with the key actors to the different elements of the tourism system such as infrastructure, superstructure and structure. As a result, the rural sector has a deficit in basic services. It is processed after identifying the problems in the socio-cultural, environmental and tourism areas through the PESTLA matrix, which allows analyzing the political, economic, social, technological, legal and environmental factors oriented to tourism. The main problems have been limited to the budget for the execution of tourism projects; The lack of supporting in rural parishes by MINTUR and environmental pollution caused by poor management of solid and liquid waste; also due to the lack of environmental awareness on the part of the inhabitants and tourists who visit the Canton. With respect to sports do not have a signaling nor with a dissemination and promotion of them. The authorities of the GAD municipal services work in the rural sectors, since there is a priority in the urban sector, working together with the parishes to promote tourism and improve the inhabitants life quality